STUDENTS PERCEPTION OF HEDONISM LIFESTYLE ON THE CIVICS LEARNING PROCESS - Gita Faolina; Berchah Piteoewas; Hermi Yanzi (FKIP Unila, 2012)
The purpose of this research was to describe the perceptions of students against the hedonism lifestyle on the civics learning process in class XI SMA Negeri 1 Terbanggi Besar then gives solutions to the teachers, the principal and parents, especially learners in SMA Negeri 1 Terbanggi Besar. The method in this research use descriptive method, with the subject the students of Class XI SMA Negeri 1 Terbanggi Besar. Sample research as many as 60 respondents. The technique of data collection using a questionnaire and analyzed using percentage techniques.Keywords: hedonism lifestyle, civics learning, behavior